2022
DOI: 10.1155/2022/5483155
|View full text |Cite|
|
Sign up to set email alerts
|

The Correlation and Copathogenesis of Coronary Aortic Sandwich and Renal Cysts

Abstract: Objective. To determine the correlation for aortic occlusion and hydronephrosis and the pathogenesis of copathogenesis. Methods. A retrospective census was established to probe the correlation with renal cysts by gathering aortic coarctation details concerning generic symptoms, diabetes, and liver and kidney profiles from 244 hospitalized aortic clinographers from April 2014 to December 2021 (study category, SG category), 150 hypertensive clients with primary hypertension attending our institution in the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%